Hibridación de espacios: el edificio hidrido como unidad integral de habitat (2020)
The arrival of the new millennium brought the expansion of new ideas and concepts in the way of doing architecture, technology is the quintessential ally of all these new proposals that fight to demonstrate that they are much more than a fashion and that they are here to stay, What is certain is that spatial hybridization is becoming a constant in the development of these new proposals in the face of the demand and expansion of cities. This emerging generation is choosing to concentrate nuclei and provide them with the greatest number of possible and additionally necessary uses where the direct impact of segregation on societies would be diminished.